2019
DOI: 10.15673/fst.v13i4.1566
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sour-Milk Healthy Beverages With the Use of Natural Herbal Nanoadditives

Abstract: Technologies of healthfull products - bioyogurts with unique characteristics have been developed. The new products are characterized by a high content of naturally occurring biologically active substances - phytocomponents of fruits and vegetables (carrots, lemons with zest, apples, Jerusalem artichoke), in particular, β-carotene, phenolic compounds, tannins, ascorbic acid, ie substances having antioxidants. Besides, they have a high content of prebiotic substances - soluble pectic substances, cellulose, inuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…All researchers suggest the potential positive effect of a plant addition in a drink on consumer health. Research on this subject was undertaken by Pavyluk et al (2019), who showed that milk drinks fortified with plant materials can be extremely attractive for people who want to follow a healthy diet. The yogurts developed by this research team based on whey with fruit and vegetable cryo-additives (apple, carrot, Jerusalem artichoke, lemon) as well as spice and nontraditional herb extracts (purple coneflower, coriander, yellow melilot, oregano) were characterized by the presence of easily digestible amino acids, significant content of biologically active substances and phytonutrients such as phenolic compounds (detoxifiers, antioxidants, and immunomodulators) in amounts much greater than the human body needs every day.…”
Section: Milk Drinks Fortified With Plant Ingredientsmentioning
confidence: 99%
“…All researchers suggest the potential positive effect of a plant addition in a drink on consumer health. Research on this subject was undertaken by Pavyluk et al (2019), who showed that milk drinks fortified with plant materials can be extremely attractive for people who want to follow a healthy diet. The yogurts developed by this research team based on whey with fruit and vegetable cryo-additives (apple, carrot, Jerusalem artichoke, lemon) as well as spice and nontraditional herb extracts (purple coneflower, coriander, yellow melilot, oregano) were characterized by the presence of easily digestible amino acids, significant content of biologically active substances and phytonutrients such as phenolic compounds (detoxifiers, antioxidants, and immunomodulators) in amounts much greater than the human body needs every day.…”
Section: Milk Drinks Fortified With Plant Ingredientsmentioning
confidence: 99%